Electrophoretic variation between the central and southern populations of the northern anchovy Engraulis mordax Girard 1854 (Engraulidae, Pisces) from Baja California, Mexico - P Díaz-Jaime; M Uribe-Alcocer; E Ayala-Duval (Ciencias Marinas, 1999)
Distinctive genetic markers of the central and southern populations of the northern anchovy Engraulis mordax were sought by electrophoretic techniques. Three samples of the central population were collected in Ensenada, Baja California, and one of the southern population in Puerto San Carlos, Baja California Sur. Although the electrophoretic separation of the hemoglobins in polyacrilamide gels were identical in both populations, the FST of the esterases loci showed significant differences between them, and the proteins of the muscle extract as well as the parvalbumins yielded some bands that were exclusive to one population or the other. These bands might prove useful as genetic markers in studies of population dynamics on which the management of this valuable fishery resource can be based.